Effects of Differing Monomer Compositions on Properties of P(3HB-co-4HB) Synthesized by Aneurinibacillus sp. H1 for Various Applications - Pospisilova, Aneta; Vodicka, Juraj; Trudicova, Monika; Juglova, Zuzana; Smilek, Jiri; Mencik, Premysl; Masilko, Jiri; Slaninova, Eva; Melcova, Veronika; Kalina, Michal; Obruca, Stanislav; Sedlacek, Petr (Polymers, 2022)
Films prepared from poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymers produced by Aneurinibacillus sp. H1 using an automatic film applicator were homogeneous and had a defined thickness, which allowed a detailed study of physicochemical properties. Their properties were compared with those of a poly (3-hydroxybutyrate) homopolymer film prepared by the same procedure, which proved to be significantly more crystalline by DSC and XRD. Structural differences between samples had a major impact on their properties. With increasing 4-hydroxybutyrate content, the ductility and release rate of the model hydrophilic active ingredient increased significantly. Other observed properties, such as the release of the hydrophobic active substance, the contact angle with water and ethylene glycol, or the surface morphology and roughness, were also affected by the composition. The identified properties predetermine these copolymers for wide use in areas such as biomedicine or smart biodegradable packaging for food or cosmetics. The big advantage is the possibility of fine-tuning properties simply by changing the fermentation conditions.
Keywords: mechanical properties; P(3HB-co-4HB); polyhydroxyalkanoates (PHA); crystallinity; Aneurinibacillus sp. H1; surface morphology; active ingredients release